Optical soliton molecular complexes in a passively mode-locked fibre laser - Z. Q. Wang (Nature Portfolio, 2019)
It has recently been shown that optical solitons can form stably bound states, so-called soliton molecules. Here, Wang et al. demonstrate stable soliton molecule complexes and explore the different bonds represented by the inter- and intra-molecular coupling.